Faktor Psikologis, Gaya Hidup, dan Kelompok Referensi pada Generasi Z terhadap Minat Menabung di Bank Syariah Indonesia - Maulana Rizki; Tamamudin (Journal Of Islamic Economics And Finance, 2024)
This study aims to determine the psychological factors, lifestyle, and reference groups in generation Z towards interest in saving at Bank Syariah Indonesia. This type of research is quantitative field research that emphasizes the management of numerical data through statistical methods. Generation Z in Tegal Regency was used as the population in this study. The data collection technique in this study was in the form of distributing questionnaires using a sample of 100 respondents. Lemeshow formula was used by the research in the process of determining the number of samples available, then the sample was taken using non-probability sampling method. The results of this study indicate that through the t test method (partial) all independent variables have a significant effect on interest in saving money as the dependent variable. Then, through the f test (simultaneous) together the independent variables have a significant effect on saving interest.